2021
DOI: 10.1371/journal.pone.0257275
|View full text |Cite
|
Sign up to set email alerts
|

The possible mediatory role of adipokines in the association between low carbohydrate diet and depressive symptoms among overweight and obese women

Abstract: Background Previous studies showed the possible association between obesity, dietary pattern, and depressive symptoms. Due to the lack of enough data to confirm the association of obesity and depression in the Middle East, here, we aimed to explore the possible mediatory role of adipokines Galectin-3, transforming growth factor-beta (TGF-β), and endothelial plasminogen activator inhibitor (PAI-1) in the association between low carbohydrate diet (LCD) and depressive symptoms. Methods A total of 256 women aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Depression was independently associated with higher levels of Gal-3 in patients with type 1 diabetes mellitus (DM) ( Melin et al, 2020 ). Gal-3 could be included in the link between obesity and depressive symptoms in overweight and obese women ( Setayesh et al, 2021 ). According to the current state of knowledge, Gal-3 activity in cognitive functioning must be viewed from the standpoint of its role in systemic changes regulating inflammatory and metabolic processes of the whole organism.…”
Section: Galectin-3 and Cognitionmentioning
confidence: 99%
“…Depression was independently associated with higher levels of Gal-3 in patients with type 1 diabetes mellitus (DM) ( Melin et al, 2020 ). Gal-3 could be included in the link between obesity and depressive symptoms in overweight and obese women ( Setayesh et al, 2021 ). According to the current state of knowledge, Gal-3 activity in cognitive functioning must be viewed from the standpoint of its role in systemic changes regulating inflammatory and metabolic processes of the whole organism.…”
Section: Galectin-3 and Cognitionmentioning
confidence: 99%
“…Adipokine levels such as elevated omentin-1 (a recently identified adipokine) were found to be altered in patients with HS compared with controls. 48 Results from clinical studies and meta-analyses of patients with depression also have demonstrated that adipokines are dysregulated in this population, 49,50 which may be another potential genetic link between depression and HS.…”
Section: Commentmentioning
confidence: 92%
“…Specifically, leptin plays a fundamental role in energy homeostasis and is produced by adipose tissue. This adipokine plays an essential role in appetite regulation through the arcuate nucleus of the hypothalamus in the central nervous system [135]. This regulation allows metabolic expenditure to be increased and the sensation of hunger to be reduced.…”
Section: Adipokines and Mental Diseasementioning
confidence: 99%